Hybrid Floating Photovoltaic - Hydropower Potential Utilization in Indonesia. Issue 1 (1st December 2022) - Aminuddin,; Pranoto, B; Irsyad, M I A; Sihombing, A L; Nurliyanti, V
Abstract: Most countries mitigate climate alter impacts by deploying renewable energy to decarbonize their energy system. One of the emerging renewable energy options is the integration of floating photovoltaic (FPV) and hydropower. The FPV has higher efficiency and helps to reduce evaporation and offset hydropower production during the dry season. Conversely, hydropower can overcome intermittent solar production due to its flexibility. Our study aims to estimate the energy potentials from FPV plants and hydropower integrations in Indonesia. As result, the country has 5, 807 potential reservoirs for FPV and 26 hydropower plants with a reservoir area with a potential utilization of more than 1 MW. Those sites are suitable for 3 GW floating power plants and 2.8 GW hydropower. And those sites can reduce CO2 emissions by 2, 911, 197 tonnes per year.